Pengaruh Tekanan Sosial terhadap Quiet Quitting Generasi Z dalam Bingkai Budaya Kerja Lokal di Kota Bogor - Risma Nur Fitria; Mirna Nur Alia Abdullah (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah Kupang, 2026)
The phenomenon of “quiet quitting” is increasingly being discussed as a form of declining work engagement, particularly among Generation Z, especially in the food and beverage sector, which is characterized by high work demands. This condition is believed to be influenced by various factors, one of which is social pressure arising within the workplace. The purpose of this study is to examine the influence of social pressure on quiet quitting among Generation Z within the framework of local work culture in the city of Bogor. This study employs an explanatory quantitative approach using a survey method. The data collection technique used is stratified random sampling, and the data obtained were then analyzed using IBM SPSS Statistics software. The results show that social pressure has a positive and significant effect on quiet quitting, with a significance value of 0.001 (<0.05) and a coefficient of determination of 20.6%. It can be concluded that social pressure is one of the factors influencing the tendency toward quiet quitting among Generation Z workers in the food and beverage sector in Bogor City.